Technique development of 3D dynamic CS‐EPSI for hyperpolarized 13C pyruvate MR molecular imaging of human prostate cancer. Issue 5 (25th March 2018) - Chen, Hsin‐Yu; Larson, Peder E.Z.; Gordon, Jeremy W.; Bok, Robert A.; Ferrone, Marcus; van Criekinge, Mark; Carvajal, Lucas; Cao, Peng; Pauly, John M.; Kerr, Adam B.; Park, Ilwoo; Slater, James B.; et al.
Abstract : Purpose: The purpose of this study was to develop a new 3D dynamic carbon‐13 compressed sensing echoplanar spectroscopic imaging (EPSI) MR sequence and test it in phantoms, animal models, and then in prostate cancer patients to image the metabolic conversion of hyperpolarized [1‐ 13 C]pyruvate to [1‐ 13 C]lactate with whole gland coverage at high spatial and temporal resolution. Methods: A 3D dynamic compressed sensing (CS)‐EPSI sequence with spectral–spatial excitation was designed to meet the required spatial coverage, time and spatial resolution, and RF limitations of the 3T MR scanner for its clinical translation for prostate cancer patient imaging. After phantom testing, animal studies were performed in rats and transgenic mice with prostate cancers. For patient studies, a GE SPINlab polarizer (GE Healthcare, Waukesha, WI) was used to produce hyperpolarized sterile GMP [1‐ 13 C]pyruvate. 3D dynamic 13 C CS‐EPSI data were acquired starting 5 s after injection throughout the gland with a spatial resolution of 0.5 cm 3, 18 time frames, 2‐s temporal resolution, and 36 s total acquisition time. Results: Through preclinical testing, the 3D CS‐EPSI sequence developed in this project was shown to provide the desired spectral, temporal, and spatial 5D HP 13 C MR data. In human studies, the 3D dynamic HP CS‐EPSI approach provided first‐ever simultaneously volumetric and dynamic images of the LDH‐catalyzed conversion of [1‐ 13 C]pyruvate to [1‐ 13 C]lactate in a biopsy‐proven prostate cancer patient with full gland coverage. Conclusion: The results demonstrate the feasibility to characterize prostate cancer metabolism in animals, and now patients using this new 3D dynamic HP MR technique to measure kPL, the kinetic rate constant of [1‐ 13 C]pyruvate to [1‐ 13 C]lactate conversion.